2019
DOI: 10.1523/eneuro.0108-19.2019
|View full text |Cite|
|
Sign up to set email alerts
|

Cellular and Network Mechanisms May Generate Sparse Coding of Sequential Object Encounters in Hippocampal-Like Circuits

Abstract: The localization of distinct landmarks plays a crucial role in encoding new spatial memories. In mammals, this function is performed by hippocampal neurons that sparsely encode an animal’s location relative to surrounding objects. Similarly, the dorsolateral pallium (DL) is essential for spatial learning in teleost fish. The DL of weakly electric gymnotiform fish receives both electrosensory and visual input from the preglomerular nucleus (PG), which has been hypothesized to encode the temporal sequence of ele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 93 publications
1
12
0
Order By: Relevance
“…In a more comprehensive study, Vinepinsky et al [ 186 ] likewise showed the presence of cells with navigation-related activity in the dorsolateral telencephalon of free-swimming goldfish, for example, “border cells”, that increase their firing rate when the fish approaches the environmental boundaries, and “velocity cells”, whose activity correlate with the fish swimming direction and speed. Additionally, Fotowat et al [ 28 ] and Trinh et al [ 204 ] found cells in the hippocampal pallium of an electrosensory gymnotiform that presumably exhibit spatial navigation-related activity. Furthermore, recently Wallach et al [ 205 ], based on electrophysiological single cell recordings in the preglomerular complex of the weakly electric fish Apteronotus leptorhynchus , have proposed a hypothetical neural mechanism to derive allocentric spatial representations from egocentric sensory information.…”
Section: Hippocampal Pallium Mechanisms For Map-like Spatial Navigation In Teleost Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…In a more comprehensive study, Vinepinsky et al [ 186 ] likewise showed the presence of cells with navigation-related activity in the dorsolateral telencephalon of free-swimming goldfish, for example, “border cells”, that increase their firing rate when the fish approaches the environmental boundaries, and “velocity cells”, whose activity correlate with the fish swimming direction and speed. Additionally, Fotowat et al [ 28 ] and Trinh et al [ 204 ] found cells in the hippocampal pallium of an electrosensory gymnotiform that presumably exhibit spatial navigation-related activity. Furthermore, recently Wallach et al [ 205 ], based on electrophysiological single cell recordings in the preglomerular complex of the weakly electric fish Apteronotus leptorhynchus , have proposed a hypothetical neural mechanism to derive allocentric spatial representations from egocentric sensory information.…”
Section: Hippocampal Pallium Mechanisms For Map-like Spatial Navigation In Teleost Fishmentioning
confidence: 99%
“…Therefore, these models propose that spatial memory is a dynamic process in which different hippocampal circuits and mechanisms sequentially engage in a time-dependent manner throughout the different phases of memory formation and remembering [ 208 , 209 , 210 , 211 , 212 , 213 ]. Interestingly, recent neuroanatomical and neurofunctional studies have evidenced the presence of both sparse input projections and highly recursive intrahippocampal circuits in the presumed teleost fish hippocampal pallium homologue [ 214 , 215 ], as well as dynamic changes in the subregional hippocampal activity throughout the spatial learning process, suggesting pattern separation and completion operations that resemble those accomplished by the mammalian dentate gyrus/CA3 network [ 183 , 204 ]. The activation and engagement of distinct components of the hippocampal pallium at separate stages of spatial memory formation and recall have been recently reported in goldfish [ 183 ].…”
Section: Hippocampal Pallium Mechanisms For Map-like Spatial Navigation In Teleost Fishmentioning
confidence: 99%
“…Temporal and spatial propagation of DL-intrinsic activity will depend on the local recurrent architecture of DL ( Fig. 2B ) (Giassi, Ellis, et al, 2012; Trinh et al, 2016) and the intrinsic dynamics of DL neurons (Trinh et al, 2019). For example, long-lasting self-chirp induced DL reverberatory activity ((i.e., >200 ms), (Trinh et al, 2019; Trinh et al, 2016) might greatly amplify overlapping female + echo chirp responses.…”
Section: Discussionmentioning
confidence: 99%
“…2B ) (Giassi, Ellis, et al, 2012; Trinh et al, 2016) and the intrinsic dynamics of DL neurons (Trinh et al, 2019). For example, long-lasting self-chirp induced DL reverberatory activity ((i.e., >200 ms), (Trinh et al, 2019; Trinh et al, 2016) might greatly amplify overlapping female + echo chirp responses. A similar scenario might apply to the effect of the reciprocal connections between DL and the globally recurrent DD network ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…After attaining the whole‐cell configuration, the resting membrane potential (RMP) was recorded for 30–60 s after which 500 ms square pulse currents of varying magnitude were injected into the cell. To characterize the slowly adapting spike threshold we encountered (see Results), we administered a ramp current injection protocol as previously described (Trinh et al., 2019). Recorded cells were held for roughly 20–45 min, depending on the health of the cell.…”
Section: Methodsmentioning
confidence: 99%